Attenuation or local wavefield amplification in the gas cloud ? - Prajapati, S. (Society of Exploration Geophysicists, 2016)
The presence of gas cloud has long been recognized as a significant problem in the seismic data processing around the world (North Sea, offshore South-East Asia). Major hydrocarbon bearing fields are affected by shallow gas clouds and therefore data quality in often suffers from serious wipeouts due to shallow gas or gas leaking from a deep reservoir. In particular, amplitudes and phases are significantly affected by attenuation or local wavefield amplification. In principle, full waveform inversion (FWI) is a suitable tool to obtain detailed subsurface properties of the Earth. FWI is a data-strategy equation based ill-posed and highly non-linear approach has proved its effectiviness in significantly improving the spatial resolution of complex problem such as gas cloud. In present study, I approached this problem using elastic wave equation with and without considering the Q-factor in gas cloud. Â© 2016 SEG.